Evaluation of Peltier Cooling Vest - Vin Klein A. Talamayan; Mharlon Jefferson S. A. Yalung; Jessie R. Balbin (Engineering Proceedings, 2025)
We incorporated a Peltier cooling system into vests for personal comfort and applications in various workplaces. We tested the Peltier cooling vest using temperature sensors and evaluated the vest’s performance. The developed Peltier cooling vest included thermoelectric cooler modules to improve cooling efficiency and comfort by using water’s heat transfer and thermal conductivity. Through testing and subjective assessments, the effectiveness of the wearable cooling system and its potential for widespread adoption were validated. Furthermore, an intelligent control algorithm was developed to maintain target temperatures. The built-in temperature sensor enabled temperature stability in the set temperature range. The average cooling response time of the Peltier cooling vest was 9.42 min. In a lower temperature range of 16 to 24 °C, the vest maintained a stable temperature. A correlation between temperature and power consumption was observed. To improve the performance, built-in Bluetooth and a graphic user interface need to be integrated. Then, the Peltier cooling vest and its technology can be used in medical and industrial settings.